The metalloendopeptidase nardilysin (NRDc) is potently inhibited by heparin-binding epidermal growth factor-like growth factor (HB-EGF). - Hospital, Véronique (2002)
Nardilysin (N-arginine dibasic convertase, or NRDc) is a cytosolic and cell-surface metalloendopeptidase that, in vitro, cleaves substrates upstream of Arg or Lys in basic pairs. NRDc differs from most of the other members of the M16 family of metalloendopeptidases by a 90 amino acid acidic domain (DAC) inserted close to its active site. At the cell surface, NRDc binds heparin-binding epidermal growth factor-like growth factor (HB-EGF) and enhances HB-EGF-induced cell migration. An active-site mutant of NRDc fulfills this function as well as wild-type NRDc, indicating that the enzyme activity is not required for this process. We now demonstrate that NRDc starts at Met(49). Furthermore, we show that HB-EGF not only binds to NRDc but also potently inhibits its enzymic activity. NRDc-HB-EGF interaction involves the 21 amino acid heparin-binding domain (P21) of the growth factor, the DAC of NRDc and most probably its active site. Only disulphide-bonded P21 dimers are inhibitory. We also show that Ca(2+), via the DAC, regulates both NRDc activity and HB-EGF binding. We conclude that the DAC is thus a key regulatory element for the two distinct functions that NRDc fulfills, i.e. as an HB-EGF modulator and a peptidase.